Analysis on the Influencing Factors of Environmental Protection Public Report - Zhang, Yiyun (Transactions on Environment, Energy and Earth Sciences, 2024)
Based on the relevant data of the national environmental protection report online unified management platform, the influencing factors of environmental protection public report was explored in this paper through SPSS linear regression analysis. In the paper, it was found that: the level of economic development, population size, investment level and trade opening level were positively related to the number of public environmental protection reports, among which, the level of economic development had the strongest correlation with the number of environmental protection reports. It was revealed that: on the whole, China’s current economic growth was still at the expense of the environment the expansion of population size had not yet produced agglomeration effect, the efficiency of environmental protection investment needed to be improved, and the level of introducing foreign advanced technology still had room for progress. Therefore, there is still a contradiction between the public's demand for a good ecological environment and the reality of environmental deterioration. We must further optimize the economic structure and population size, improve the utilization efficiency of governance funds and the level of environmental protection technology, and further encourage public participation in environmental protection.